Prematurity and language development of 9-18 months child: A correlation study - Nurul Hidayati Hariningtyas; Yuni Kusmiyati; Nur Djanah; Serap Ejder Apay (Poltekkes Kemenkes Yogyakarta, 2022)
Premature birth (gestational age <37 weeks) can cause a variety of health problems premature birth are prone for experiencing impaired children's language development in the future. This study was to know the correlation between prematurity and language development of children aged 9-18 months. This research was an observational analytic study with a retrospective cohort design (historical cohort), conducted in August 2019-April 2020. The population was all infants born at Wates General Regional Hospital (RSUD) Wates in Kulon Progo Regency in October 2018-July 2019. The sample was 96 children who were divided into 48 children in the exposed group and 48 children in the non-exposed group. The sampling technique used simple random sampling. The variables in this study were prematurity, smoking parents, maternal education, maternal occupation, and socioeconomics. The data were obtained using Google Form and Denver II forms. Data analysis used chi-square test and logistic regression. There was a correlation between the variables of prematurity with language development. After controlling for smoking parents and mother education variable have significance (p=0.015) on the dependent variable. Developmental language disorders are 3,57 times higher in children born prematurely (OR=3,571). There was no statistically significant correlation between maternal occupation and socioeconomics on language development (p=0.525; 0.277). The chance of language development disorder if the child is born prematurely and has parents who’s smoking and low maternal education is 62%. Prematurity is a risk factor for children's developmental language disorder.